Recycling of Building Interior Decoration and Renovation Waste: A Case Study in China - Wenjia Pan; Hong Zhang; Shanggang Hei; Yingjian Yang; Xifeng Xu; Chao Zhou; Baolin Huang; Haochen Xu (Buildings)
Of all the construction waste, the building interior decoration and renovation waste (D&R waste) is difficult to dispose of and recycle due to its complex components and varied producers. The goal of this study is to reveal the current situation of D&R waste disposal through case studies and put forward the correlation proposal to improve standards of D&R waste recycling. This study investigated the various stages of the D&R waste management process, including generation, collection, transportation, sorting, recycling, and landfilling. Detailed studies were conducted for (i) the composition of D&R waste and (ii) the material flow analysis (MFA) of D&R waste recycling in different cases with different sorting technology. The results show that (i) concrete, stone, and other hard inorganic materials accounted for about 35–55% of the total. Soft inorganic materials such as aerated concrete and gypsum made up 5–25%, slag 15–20%, timber 5–10%, combustible matter such as plastic, rubber, and paper 9–12%, and glass and metal 1–5%, and (ii) artificial intelligence (AI) sorting offers better sorting performance and economic advantages over manual sorting, promoting the application of artificial AI sorting equipment as important solutions to face the key challenges of D&R waste recycling.